Criteria, Indicators and Levels of Diagnosing Managerial Competence of Future Officers of Communication Units - Oleh Pavlenko (Pedagogical Discourse, 2022)
The article defines and substantiates the criteria and indicators of the formation of managerial competence of future officers of communication units of the Armed Forces of Ukraine. In the framework of the research, a criterion is defined as the measure by which it is possible to diagnose the managerial competence of future communication officers of the Armed Forces of Ukraine in the process of professional training. This allowed to obtain information about the degree of its formation in accordance with the determined indicators. It was found that the general level of formation of the specified competence depends on the degree of formation of each of its components: motivational and value, cognitive, operational and personal.On the basis of the theoretical justification of the essence and structure of the managerial competence of future communications officers, taking into account the job competencies of future officers of communication units of the Armed Forces of Ukraine, the peculiarities of the educational process at operational-tactical level of the higher military education institutions, as well as modern requirements for the content of the professional competence of officers of the Armed Forces of the Armed Forces, were distinguished criteria and indicators for diagnosing the formation of their managerial competence, which outline the main patterns of formation and relationships between the components of this competence, namely: motivational, cognitive, activity and personal. Based on the analysis and generalization of information from scientific sources, the levels of assessment of the state of formation of managerial competence of future officers of the communication units of the Armed Forces of Ukraine were determined: low, medium and high.